Pengaruh Pemanfaatan Perpustakaan Sekolah Terhadap Hasil Belajar Siswa - Melindawati A Anunu; Usman Moonti; Sudirman Sudirman; Melizubaida Mahmud; Roy Hasiru (State University of Gorontalo, 2023)
The present study aimed to determine the effect of the utilization of the school library on students’ learning outcomes in the economics subjectin class X of social sciences at SMA Negeri 1 Suwawa Timur. This study employed a quantitative approach with a survey research method. The data used were primary data obtained from distributing questionnaires to students at SMA Negeri 1 Suwawa Timur, with a total sample of 41 respondens. At the same time, the data analysis technique used simple linear regression. The analysis results of the coefficient of determination in the table denoted that the adjusted coefficient of determination or the R-Squared value was 0,215 or 21,5%. This value signified that 21,5% of the variability of students’ learning outcomes could be explained by the variable of the utilization of the school library. In comparison, the remaining 78,5% was explained by other variables that were not examined in this study.